1998
DOI: 10.1046/j.1365-3156.1998.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni infection in a recently exposed community in Senegal: lack of correlation between liver morphology in ultrasound and connective tissue metabolites in serum

Abstract: SummaryFour hundred and seventy villagers of Ndombo, a village with recently established intensive transmission of Schistosoma mansoni in the Senegal River Basin, were enrolled in a study with the intention to assess hepatosplenic morbidity. All patients were examined parasitologically and by ultrasound. Hepatic fibrosis serum markers were determined in 153 adult patients (aminoterminal propeptide of procollagen type III, hyaluronan and laminin). By ultrasound, about 60% of the patients showed early stages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 52 publications
0
15
1
Order By: Relevance
“…Ricard-Blum et al (1999) found a good correlation between HA and ultrasound scores of fibrosis in an endemic area for schisto- somiasis in Madagascar. Burchard et al (1998) found no correlation and suggested that the increase of serum HA levels was actually related to inflammatory activity or liver function alterations that are absent in schistosomiasis, rather than to fibrosis itself. Yet, WHO patterns for ultrasound in schistosomiasis (Niamey Working Group 2000) have not been employed in the investigation of non-invasive markers of fibrosis.…”
Section: Discussionmentioning
confidence: 94%
“…Ricard-Blum et al (1999) found a good correlation between HA and ultrasound scores of fibrosis in an endemic area for schisto- somiasis in Madagascar. Burchard et al (1998) found no correlation and suggested that the increase of serum HA levels was actually related to inflammatory activity or liver function alterations that are absent in schistosomiasis, rather than to fibrosis itself. Yet, WHO patterns for ultrasound in schistosomiasis (Niamey Working Group 2000) have not been employed in the investigation of non-invasive markers of fibrosis.…”
Section: Discussionmentioning
confidence: 94%
“…This classification does not take into consideration the age or height of the patients (Burchard et al 1998). It is possible that adjusting a body-height dependent reference value, as proposed by the Niamey Working Group (2000), the ultrasound specificity could be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors, while studying intestinal or hepatointestinal patients, did not observe any significant difference in the serum levels of PIIINP that correlated with the presence or intensity of infection (Kardorff et al 1999), egg-positive individuals (Tanabe et al 1989) or fibrosis scores (Kardorff et al 1997, Burchard et al 1998, Ricard-Blum et al 1999. -Kardorff et al (1997-Kardorff et al ( , 1999 demonstrated that the procollagen IV peptide did not correlate with the presence or intensity of schistosomiasis infection, but it was significantly correlated with liver fibrosis, splenomegaly, portal vein dilatation and the presence of portosystemic collaterals.…”
Section: Procollagen Type III Amino-terminal Peptide (Pii-inp)mentioning
confidence: 94%
“…A reduction in serum HA level was also revealed following early treatment with praziquantel in patients with the intestinal form of the disease (Hassanein et al 1997). Burchard et al (1998), studying 153 patients in Senegal with schistosomotic hepatic fibrosis, found no changes in patient levels of HA, laminin or PIIINP. A possible reason underlying these results could be that 60% of patients showed early stages of hepatic involvement with US, while only 3% presented with HS disease.…”
Section: Serum Type VI Collagenmentioning
confidence: 98%
See 1 more Smart Citation